BUILDING STRONGER BUSINESS EDUCATION THROUGH THE INCORPORATION OF INDUSTRY 4.0 TECHNOLOGIES (NAU Journal of Technology and Vocational Education, 2026)
This study examined building stronger business education through the incorporation of industry 4.0 technologies. The study employed survey research design. The population of study consisted of 200 business education lecturers in tertiary institutions in South East Nigeria. The study employed multi-stage sampling technique to select 100 Business Education lecturers. Structured questionnaire was used as the instrument of data collection. Mean rating was employed to analyze the data collected. T-test statistics was conducted to test the hypothesis at 0.05 level of significance. The findings of the study showed that Artificial Intelligence, Big Data analysis, IoT, virtual reality and cloud computing were the types of industry 4.0, technologies that could be incorporated in business education curriculum to prepare business education students for work in this age of high digital transformation. Also, the study found that industry 4.0 technologies have prospect of improving business education programme by fostering new skills like digital literacy, critical thinking and shifting towards interdisciplinary and experiential learning methods such as virtual/augmented reality and project-based learning and better prepare business education students for the rapid changing demands of the present-day industrial sectors by making the course more adaptive, data-driven and collaborative. Thus, the study concluded that there is mean difference between male and female teachers’ opinions on the prospects of business education programme with the integration of industry 4.0, technologies in the classroom. Therefore, the study recommended among others that Government should provide adequate funds budget allocation to tertiary institutions for procurement of industry 4.0 infrastructures.
Keywords: Building Stronger; Business Education; Incorporation; Industry, 4.0 Technologies